The Roche vault performed by elite gymnasts: Somersaulting technique, deterministic model, and judges` scores - Takei, Y. (Journal of Applied Biomechanics, 2007)
The purpose of the study was to determine the mechanical variables that are related to successful post-flight somersaulting performance of the Roche vault. The 23 Roche vaults performed during the 2000 Olympic Games were filmed by a 16-mm camera operating at 100 Hz. The 2-D direct linear transformation technique was used for spatial calibration. Approximately 60 frames were digitized per vault. The method of Hay and Reid (1988) was used to develop a deterministic model to identify the mechanical variables that govern linear and angular motions of the vault. Correlational analysis was used to establish the strength of the relationship between the mechanical variables identified and the judges` scores. Significant correlations indicated that the higher judges` scores were negatively related to five mechanical variables and positively related to seventeen variables in the model. The normalized horizontal displacement of body center of mass (CM) from the knee grasp to the peak of post-flight was the best single predictor of the judges` score and accounted for 50% of variation in the judges` score. Finally, the landing point deductions and the official horizontal distance of post-flight collectively accounted for 86% of the variance in the judges` scores.